Memory and Identity in Crisis: A Comparative Study of Rakesfall and The Memory Police (SCHOLARS: Journal of Arts & Humanities, 2025)
This paper examines how identity, memory, and loss are represented through the dislocation of self and the fragmentation of reality in Vajra Chandrasekera’s Rakesfall and Yōko Ogawa’s The Memory Police. The primary objective is to explore how both narratives construct dystopian landscapes where personal and collective memories are destabilized, and individual subjectivity is continuously eroded. This paper examines how characters in Rakesfall and The Memory Police navigate systems of erasure that distort their sense of identity, memory, and belonging. Using Homi K. Bhabha’s concept of the unhomely and Cathy Caruth’s trauma theory, the study analyzes how both novels portray the psychological consequences of living in environments where history is suppressed and the boundaries between self and society collapse. The absence of stable spatial and temporal coordinates in these narratives disrupts traditional storytelling and reflects the protagonists’ inner fragmentation. As memory fades and reality becomes unstable, the characters experience a profound sense of dislocation, and presents how trauma unsettles not only the mind but also the narrative form itself. The study, further, argues that Rakesfall and The Memory Police foreground a crisis of identity rooted in the unreliability of memory and the impossibility of stable selfhood in fragmented worlds. Both narratives highlight how authoritarian structures manipulate memory and perception, and ultimately leads to an existential disconnection from time, place, and self.